Peran Ayah dalam Membentuk Emosi dan Sosialisasi Anak Usia Dini dalam Perspektif Teori Erikson dan Vygotsky - Diyah Andini Kusumastuti; Ani Ani (Inovasi Pendidikan dan Anak Usia Dini, 2026)
Social emotional development in early childhood is an important foundation for children's psychological and social functioning in later stages of development. This process is greatly influenced by the quality of interactions within the family environment, including the level and quality of the father's involvement in parenting. Although various studies show that fathers play a significant role in shaping children's emotional regulation, independence, and social competence, studies that systematically integrate the role of fathers within the framework of psychosocial and sociocultural development theory are still relatively limited. This study aims to critically analyze the role of fathers in shaping the emotions and socialization of early childhood based on the perspectives of Erik Erikson's psychosocial development theory and Lev Vygotsky's sociocultural theory. This study uses a qualitative approach with a Literature Study Review (LSR) method of reputable national and international journal articles, academic books, and scientific proceedings published in the period 2020–2025. The data were analyzed through thematic synthesis and conceptual analysis. The results of the study show that consistent, responsive, and supportive father involvement contributes significantly to the development of emotional regulation, self-confidence, social initiative, and adaptive social interaction skills in children. These findings confirm the relevance of Erikson and Vygotsky's theories and provide theoretical and practical implications for the development of family parenting patterns and early childhood education policies that encourage optimal father involvement.